2014
DOI: 10.2135/cropsci2013.08.0522
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of EST‐SSR Markers in Cluster Bean (Cyamopsis spp.)

Abstract: Cluster bean, or guar, [Cyamopsis tetragonoloba (L.) Taub] is an important industrial crop. At present there are no marker resources or linkage maps available for this crop. Development of molecular markers is essential for accelerating genetic studies and breeding in guar. In the present study, mining of simple sequence repeat (SSR) sequences from 16,476 expressed sequence tags (ESTs) of guar was done using the microsatellite (MISA) identification tool. A total of 907 SSR‐containing sequences were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
(37 reference statements)
5
12
0
Order By: Relevance
“…A total of 5773 potential SSRs were identified with an average of one SSR per 7.31 kb in the unigenes. This result was consistent with the previous EST-SSR report in guar with occurrence (kb/SSR) of 7.9 (Kumar et al, 2016 ) while, Kuravadi et al reported the occurrence of 4.1 using the same dataset (Kuravadi et al, 2014 ). The occurrence of genic-SSR was also comparable to 8.4 in pigeonpea, 3.4 in rice, 5.4 in wheat, and 7.4 in soybean (Cardle et al, 2000 ; Peng and Lapitan, 2005 ; Dutta et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A total of 5773 potential SSRs were identified with an average of one SSR per 7.31 kb in the unigenes. This result was consistent with the previous EST-SSR report in guar with occurrence (kb/SSR) of 7.9 (Kumar et al, 2016 ) while, Kuravadi et al reported the occurrence of 4.1 using the same dataset (Kuravadi et al, 2014 ). The occurrence of genic-SSR was also comparable to 8.4 in pigeonpea, 3.4 in rice, 5.4 in wheat, and 7.4 in soybean (Cardle et al, 2000 ; Peng and Lapitan, 2005 ; Dutta et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…Marker assisted breeding, especially with SSRs and SNPs, has given excellent results in several other crops (Rafalski, 2002 ; Kesawat and Kumar, 2009 ; Hiremath et al, 2012 ). Such breeding programs have not been possible in guar due to the lack of sufficient number of SSRs (Kuravadi et al, 2014 ; Kumar et al, 2016 ) and the complete absence of SNPs. This has happened due to the limited availability of genetic resources in this crop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No primer pairs were designed for 31,913 (29.02%) SSR loci. An average of one SSR per 5.88kb genome sequence was developed in this study; similar observations were reported by previous authors [32,33]. However, the average size (kbp) may be varied depending upon the size of datasets (genes, contigs, and scaffolds), program or parameters [34].…”
Section: Ssrs Development Characterization and Validationsupporting
confidence: 72%